70.1k views
4 votes
1.)What number needs to be added to both sides of the equation in order to complete the square? x2+16x=18

answer is 64

x^2+16x+64=18+64

2.)Solve for x over the complex numbers.

x2+10x+41=0

answer is x=-5+4i and -5-4i

3.)What is the factored form of the expression over the complex numbers?

16x2+9y2
answer is (4x+3iy)(4x-3iy)

2 Answers

3 votes

Answer:

all of your answers are correct

1.) 64

2.) x= -5+4i and x= -5-4i

3.) (4x+3iy)(4x-3iy)

User Unbreakable
by
5.7k points
6 votes

Answer:

1.

When we are completing squares, we need to divide by 2 the linear term and then find its square power, that's the term we need to add on both sides of the equality, as follows


((16)/(2))^(2) =(8)^(2)=64

Basically, we need to add the number 64 both sides


x^(2) +16x+64=18+64

2.

The given equation is


x^(2) +10x+41=0

We need to apply the quadratic formula to solve this equation


x_(1,2) =\frac{-b(+-)\sqrt{b^(2)-4ac } }{2a}

Where
a=1,
b=10 and
c=41. Replacing these values, we have


x_(1,2) =\frac{-10(+-)\sqrt{10^(2)-4(1)(41) } }{2(1)}\\x_(1,2) =(-10(+-)√(100-164 ) )/(2)=(-10(+-)√(-64) )/(2)

There we need to use complex number, to transform the subradical number in a positive number


x_(1,2)=(-10(+-)√(64)i )/(2)=(-10(+-)8i)/(2)\\ x_(1,2)=-5(+-)4i

Therefore, the complex solutions are


x_(1)=-5+4i\\ x_(1)=-5-4i

3.

The given expression is


16x^(2) +9y^(2)

To solve this expression, remember that
i=√(-1)

First, we expresse both squares uniformly,


16x^(2) +9y^(2)=(4x)^(2)+(3y)^(2)

But, we know that
-(-1)=1, so


(4x)^(2)+(3y)^(2)=(4x)^(2)-(-1)(3y)^(2)

Then,


(4x)^(2)-(-1)(3y)^(2)=(4x)^(2)-(3y)^(2)i^(2), because
i^(2)=-1

Therefore, the expression with complex numbers is


(4x)^(2)-(3iy)^(2)\\\therefore (4x+3iy)(4x-3iy)

User Thedk
by
7.0k points